Penggunaan Model Pembelajaran STAD Dalam Meningkatkan Hasil Belajar IPA - Rahelina Rahelina (JURNAL GLOBAL EDUKASI, 2021)
Abstract: Classroom action research generally aims to improve the quality of learning for fourth grade students of SDN 016526 Huta Bagasan. specifically aims to: 1. Use STAD Learning Methods in Increasing Interest and Achievement of Human Skeletal Material and Five Senses in Science Subjects for Class IV Students of SDN 016526 Huta Bagasan Kec. Bandar Pasir Mandoge TP. 2019/2020; 2. Describe the management of science learning. This classroom action research was conducted in 2 cycles, each cycle consisting of planning, acting, observing and reflecting. The classroom action research was carried out in class IV SDN 016526 Huta Bagasan, totaling 25 students. The subjects of this study were fourth grade science teachers and fourth grade students of SDN 016526 Huta Bagasan. Data were collected through observation, interviews, tests, and study documentation. Keywords: human senses; STAD Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas IV SDN 016526 Huta Bagasan. secara khusus bertujuan untuk: (1) Menggunakan Metode Pembelajaran STAD Dalam Meningkatkan Minat dan Prestasi Belajar Materi Rangka dan Panca Indra Manusia Pelajaran IPA Siswa Kelas IV SDN 016526 Huta Bagasan Kec. Bandar Pasir Mandoge TP. 2019/2020; (2) Mendeskripsikan pengelolaan pembelajaran IPA. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Penelitian tindakan kelas dilaksanakan dikelas IV SDN 016526 Huta Bagasan yang berjumlah 25 orang siswa. Subjek penelitian ini adalah guru IPA kelas IV dan siswa kelas IV SDN 016526 Huta Bagasan, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Kata Kunci: panca indra manusia; STAD